Magnetic Resonance Characterization of Cardiac Adaptation and Myocardial Fibrosis in Pulmonary Hypertension Secondary to Systemic-To-Pulmonary Shunt. (September 2016) - Pereda, Daniel; García-Lunar, Inés; Sierra, Federico; Sánchez-Quintana, Damián; Santiago, Evelyn; Ballesteros, Constanza; Encalada, Juan F.; Sánchez-González, Javier; Fuster, Valentín; Ibáñez, Borja; García-Álvarez, Ana
Abstract : Background—: Pulmonary hypertension (PH) and right ventricular (RV) dysfunction are strong predictors of morbidity and mortality among patients with congenital heart disease. Early detection of RV involvement may be useful in the management of these patients. We aimed to assess progressive cardiac adaptation and quantify myocardial extracellular volume in an experimental porcine model of PH because of aorto-pulmonary shunt using cardiac magnetic resonance (CMR). Methods and Results—: To characterize serial cardiac adaptation, 12 pigs (aorto-pulmonary shunt [n=6] or sham operation [n=6]) were evaluated monthly with right heart catheterization, CMR, and computed tomography during 4 months, followed by pathology analysis. Extracellular volume by CMR in different myocardial regions was studied in 20 animals (aorto-pulmonary shunt [n=10] or sham operation [n=10]) 3 months after the intervention. All shunted animals developed PH. CMR evidenced progressive RV hypertrophy and dysfunction secondary to increased afterload and left ventricular dilatation secondary to volume overload. Shunt flow by CMR strongly correlated with PH severity, left ventricular end-diastolic pressure, and left ventricular dilatation. T1-mapping sequences demonstrated increased extracellular volume at the RV insertion points, the interventricular septum, and the left ventricular lateral wall, reproducing the pattern of fibrosis found on pathology. Extracellular volume at the RV insertion points strongly correlated with pulmonary hemodynamics and RV dysfunction. Conclusions—: Prolonged systemic-to-pulmonary shunting in growing piglets induces PH with biventricular remodeling and myocardial fibrosis that can be detected and monitored using CMR. These results may be useful for the diagnosis and management of congenital heart disease patients with pulmonary overcirculation.